خوارزمية لترتيب المحتوى المخبأ للتمييز بين المحتوى الجيد والخبيث في شبكات المعلومات المركزية((ICN - أحمد, أحمد; العاتكي, طلال; عاقل, أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
Named Data Network is an ICN (Information Central Network) architecture designed to be an Internet architecture that is designed to address some of the limitations caused by the use of IP. NDNs use the drag form to distribute content where content is first explicitly requested before you deliver it, showing the effectiveness of this form by aggregating the conflicting requests for the same content and temporarily storing that content on the router. Although it reduces latency and increases bandwidth usage, router caching makes the network vulnerable to new attacks on the cache by injecting and counterfeiting malicious content to replace good content and placing it in the router cache to be a candidate for customer requests. Our research aims to provide a mechanism to protect content hidden in the cache memory of routers so as to prevent malicious content poisoning attacks by malicious providers. This mechanism relies on the order of copying the content in a priority that increases and decreases according to users' opinions. We have conducted a series of experiments on the NDNSIM emulator within the NS3 environment, and these experiments have shown that our algorithm is capable of preventing these attacks. تعتبر شبكات البيانات المسمّاة (Named Data Network) NDN إحدى معماريات شبكات المعلومات المركزية ICN (Information Central Network) ، والتي صممت لتكون بنية انترنت مرشحة لمعالجة بعض القيود التي يسببها استخدام بروتوكول الانترنت IP . تستخدم شبكات الــ NDN نموذج السّحب (Pull Mode) لتوزيع المحتوى، حيث يتم أولاً طلب المحتوى بشكل صريح قبل أن تقوم بتسليمه، تظهر فعالية هذا النّموذج من خلال تجميع الطّلبات المتباعدة لنفس المحتوى وتخزين هذا المحتوى بشكل مؤقت على الموجّه. على الرّغم من أنَ التّخزين المؤقت في أجهزة التّوجيه يقلل زمن الوصول ويزيد من استخدام النّطاق الترددي إلا أنّه يجعل الشّبكة عرضة لهجمات جديدة على ذاكرة التّخزين المؤقت من خلال حقن محتويات خبيثة وتزييفها لتكون بديلاً للمحتويات الجيّدة، ووضعها ضمن ذاكرة التّخزين المؤقت للموجّه لتكون مرشحة للطّلبات القادمة من الزّبائن. يهدف بحثنا إلى تقديم آليّة لحماية المحتوى المخبأ في الذّاكرة المؤقتة لأجهزة التّوجيه بحيث نمنع هجمات تسميم المحتوى بنسخ خبيثة من قبل المزودين السّيئين، تعتمد هذه الآلية على ترتيب نسخ المحتوى وفق أولويّة تزيد وتنقص حسب آراء المستخدمين. قمنا بإجراء مجموعة من التّجارب على المحاكي NDNSIM ضمن بيئة الــ NS3 ، وقد بيّنت هذه التّجارب أنّ الخوارزمية المقترحة قادرة على منع هذه الهجمات.